An overview of insulin therapy in pharmacotherapy of diabetes mellitus type I - Alotaibi, Abdulkareem; Sultan, Bashayer Al; Buzeid, Reem; Almutairi, Mohammad; Alghamdi, Eman; Aldhaeefi, Maram; Khogheer, Yaser; Albareqi, Mohammad (International Journal Of Community Medicine And Public Health, 2018)
Type 1 diabetes mellitus is a chronic disease, which characterizes itself with body’s inability to produce insulin from pancreas. This condition can happen from different autoimmune processes, which subsequently leads into destruction of beta cells in pancreas, the cells responsible for production of insulin. This condition account for about 5-10% of all different forms of diabetes, which should be taken very seriously since its incidence seems to be increasing worldwide and it can result in different devastating short and long-term complications. Management and approaches in patients with type 1 DM is of major concern worldwide since in the lack of proper management these patients cannot survive. Therefore, it is very important to have a multidisciplinary health management team that can have full focus on every aspect of this condition from continuous glucose monitoring, meal planning, screening for different complications to insulin therapy, which is the mainstay in treatment of patients in this group. American Diabetes Association (ADA) suggests using patient’s age in establishment of glycaemic goals, with targets for pre-prandial, bedtime and haemoglobin A1c levels. It is very important to educate patients on how to adjust the level of their insulin injection according to the amount of carbohydrate intake, premeal blood glucose, and anticipated activity. Insulin is and will remain the most important treatment approach in patients suffering from type 1 DM. According to recommendations of ADA, it is best when patients with type 1 DM are treated with multiple daily doses of insulin injections, such as three to four daily basal and prandial injections, or continuous subcutaneous insulin infusion devices should be used.